Laudes Europae: Świat, Europa i Rzym (Manilius, Astronomica IV 658-695) - Rudnicka, Justyna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The first Latin source containing a complete description of the orbis terrarum is the Astronomica of Manilius, which originates from the end of the Augustan principate. This description is an introduction to an exposition devoted to the geography of the Zodiac.
Keywords: Manilius; Astronomica; orbis terrarum; geography; astrology